Enhanced Cleaning, Enhanced Healing: A Systematic Review of Advances in Endodontic Irrigation - Shubhi Gupta; Karunakaran Venkataraman Jeyaraman; M. Deepthi; Rohan Shinkre; Neha Singh; Sagar Shah (Journal of Pharmacy and Bioallied Sciences)
Background: Effective irrigation is crucial for successful endodontic treatment, ensuring debris removal, disinfection, and biofilm elimination. This systematic review analyzes recent advances in endodontic irrigants and activation systems. Materials and Methods: A comprehensive search of PubMed, Scopus, Web of Science, and Google Scholar was conducted to identify relevant studies published between 2015 and 2025. Results: Emerging irrigants, including nanoparticle-based solutions, herbal formulations, and photoactivated disinfectants, demonstrate promising antimicrobial and biocompatibility properties. Advanced irrigation activation techniques, such as ultrasonic, laser-activated, and multisonic irrigation, enhance root canal debridement efficacy. Conclusions: This review highlights the strengths and limitations of recent advancements in endodontic irrigation, providing insights into their clinical implications and future research directions.